2018
DOI: 10.1002/pc.24805
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene biocomposites reinforced with bamboo particles and ultrafine bamboo‐char: The effect of blending ratio

Abstract: Bamboo particles (BPs) and ultrafine bamboo‐char (UFBC) were introduced into polypropylene (PP) biocomposites by melt‐blending and injection molding, to improve the mechanical and thermal properties of PP matrix. The maximum tensile strength of 30.59 MPa was obtained when the ratio was 70/25/5, which was improved by 30% than that of pure PP. The maximum tensile modulus of 460.13 MPa was achieved when the ratio was 70/20/10, which was enhanced by 109%, 35% and 24% than that of neat PP, PP/BP (70/30), and PP/UFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The thickness and total length of the specimen for tensile were 4 and 150 mm, respectively. Three specimens were tested [18,19].…”
Section: Mechanicalmentioning
confidence: 99%
“…The thickness and total length of the specimen for tensile were 4 and 150 mm, respectively. Three specimens were tested [18,19].…”
Section: Mechanicalmentioning
confidence: 99%
“…Utilization of processing waste materials as biochar feedstock closes the loops of production making it a circular and sustainable process [ 9 ]. S. Zhang, Yao, Zhang, & Sheng, 2018 [ 10 ] used bamboo to produce biochar, as filler in the composites. Bartoli et al (2020) [ 11 ] used olive pruning as raw material for production of biochar used in manufacture of biochar filled epoxy composites.…”
Section: Introductionmentioning
confidence: 99%
“…In view of excellent physical characteristics and surface properties, biochar carbon materials were utilized as reinforcement in polymer composites. [16][17][18] Few works pertaining to the use of biochar as a reinforcement can be cited in. [19,20] These reports used biochar in neat epoxy and fiber glass epoxy as a reinforcement and observed that the developed composites possess excellent mechanical and thermal properties comparative to the neat epoxy.…”
Section: Introductionmentioning
confidence: 99%